Larry Aitken audio recordings - Aitken, Larry; Jackson, Jim (1980)
This collection consists of audio recordings of Larry Aitken (Bezhigoogahbow), a distinguished Ojibwe elder, teacher, and traditional knowledge keeper of Leech Lake, Minnesota. The recordings include numerous public speeches, classroom lectures and discussions, and interviews on Anishinaabe spiritual teachings, health, psychology, cultural strength, history, and language. A number of recordings were made with Aitken's teacher, Jim Jackson, a medicine man and traditional knowledge keeper with whom Aitken worked for 17 years.